Antithrombin Administration During Intravenous Heparin Anticoagulation in the Intensive Care Unit: A Single-Center Matched Retrospective Cohort Study. (January 2018) - Beyer, Jacob T.; Schoeppler, Kelly E.; Zanotti, Giorgio; Weiss, Gregory M.; Mueller, Scott W.; MacLaren, Robert; Fish, Douglas N.; Kiser, Tyree H.
Unfractionated heparin (UFH) is a frequently utilized indirect anticoagulant that induces therapeutic effect by enhancing antithrombin (AT)-mediated procoagulant enzyme inhibition. In suspected heparin resistance (HR) during cardiopulmonary bypass, AT activity may be decreased and AT supplementation helps restore UFH responsiveness. The benefit of AT supplementation in HR over longer durations of UFH therapy is unclear. The objective of this study was to describe and evaluate the use of AT III concentrate in the intensive care units (ICUs) at our institution for improving UFH therapy response over 72 hours. A total of 44 critically ill patients were included in the analysis—22 patients received at least 1 dose of AT and 22 patients received no AT. Thirty (68.2%) of the 44 patients were receiving mechanical circulatory support. Baseline characteristics were similar between groups. The average AT activity prior to AT supplementation was 57.9% in the treatment group, and the median cumulative dose of AT was 786.5 U (9.26 U/kg) per patient. There were no significant differences observed in proportion of time spent in therapeutic range (31.9% vs 35.2%, P = .65), time to therapeutic goal (16.5 vs 15.5 hours, P = .97), or patients who experienced a bleeding event (5 vs 5, P = .99) between groups. In conclusion, AT supplementation had minimal impact on anticoagulant response in this cohort of ICU patients with mild to moderate HR receiving a prolonged UFH infusion. Additional research is needed to define AT activity targets and to standardize AT supplementation practices in patients receiving prolonged heparin infusion.